Prevalence and factors associated with adequate dietary diversity among pregnant women in Nekemte town, Western Ethiopia, 2021 - Bikila, Haile; Ariti, Berhanu Tessisa; Fite, Meseret Belete; Sanbata, Jabessa Hatahu (Frontiers in Nutrition, 2023)
Background: Dietary diversity refers to increasing the consumption of a variety of foods.Consumption of diversified food during pregnancy enables adequate intake of eleven important micronutrients. Inadequate dietary intake during pregnancy is the major determinant factor in the risk of giving low birth weight infants. It is capable of ensuring adequate intake of essential nutrients that can promote good physical health and mental development. Pregnant women require more protein, iron, iodine, vitamin A, folate, and other nutrients. Adequate intake of fruit, vegetables, and animal products throughout the life cycle helps ensure that women enter pregnancy and lactation without deficiencies. Micronutrient deficiency and protein, carbohydrate, and fat intake imbalances are also linked to an increased risk of chronic disease.A community-based cross-sectional study was conducted among 475 pregnant women in the town. We used a systematic random sampling technique. Data was collected through face-to-face interviews by trained data collectors using a validated questionnaire. Before being exported to STATA version 14, data were entered into epidata version 3.1, cleaned, coded, and checked for missing values. Results from bivariable analysis of P values less than 0.25 were moved to 1ii multivariable binary logistic regression model for analysis. Finally, multivariable logistic regression with P values of less than 0.05 was considered as statistically significant.The Prevalence of adequate dietary diversity was 43.6% (95% CI; 39.1-48.1). Household had rich wealth index Adjusted odd ratio (AOR=3.17; 95%Confidence Interval =1.60-6.28), had attended antenatal (AOR=2.16; 95%CI=1.22-3.84) and women who were governmental employee (AOR=1.87; 95%CI=1.01-3.48) were positively associated with adequate dietary diversity. On the other hand, food insecure households (AOR=0.34; 95%CI=0.17-0.66), had not changed meal frequency (AOR=0.613; 95%CI=0.38-0.99) and being third trimester (AOR=0.40; 95%CI=0.20-0.81) were negatively associate with adequate dietary diversity during pregnancy.The finding showed a low prevalence of adequate dietary diversity among pregnant women in the town. Wealth index, antenatal care, women"s occupation, household food insecurity, gestational age, and not changing meal frequency were identified as factors associated with adequate dietary diversity. Therefore, multi-sectoral collaboration is needed to enhance the dietary diversity of pregnant women by promoting women's employment and strengthening sustainable incomegenerating activities.